A literature review on V2X communications security: Foundation, solutions, status, and future - Zuobin Ying; Kaichao Wang; Jinbo Xiong; Maode Ma (IET Communications)
Abstract With the refinement and development of the Vehicle to Everything (V2X) concept, its security issues have gradually come to the fore, revealing many security risks and increasing security requirements for V2X, and many protective measures have likewise emerged. The article first introduces the development history of the past Internet of Vehicles(IoV), summarizes some common V2X security threats, surveys the security technologies used for V2X communication, and outlines the development of each technology and the proposed security protocols in the last 3 years. Due to the different advantages and disadvantages of previous protection schemes, the idea of using National Cryptography to supplement the security scheme or designing a new security scheme article based on the National Cryptography Algorithms((AKA SM algorithms) is proposed. The survey then introduces the SM2, SM3, SM9, and ZUC algorithms, describes the development and application of the SM commercial algorithm in recent years, and finally, statistics and introduces the part of the development process of the security protocols currently used in IoV regarding the SM algorithms and gives some application prospects.